Panel obywatelski jako instrument włączenia mieszkańców w sprawy miasta - Brzeziński, Kamil; Jurczak, Tomasz; Rzeńca, Agnieszka; Agnieszka Gralak (Public participation in urban climate policy making: The example of Lodz, 2024)
The last decade has been a period of growing popularity of public participation and innovative instruments for involving residents in co-decision processes. Processes inspired by the concept of deliberative democracy are increasingly being used in practice. One of such mechanism is the citizens’ assemblies, which are willingly being utilized by local authorities in large Polish cities. The article aim is to synthetically present the idea of a citizen assembly and to analyse its potential strengths and drawbacks as an instrument to involve citizens in decision-making processes.